Dysphagia, hypothyroidism, and osteoradionecrosis after radiation therapy for head and neck cancer - Ranta Pihla; Kytö Eero; Nissi Linda; Kinnunen Ilpo; Vahlberg Tero; Minn Heikki; Haapio Eeva; Nelimarkka Lassi; Irjala Heikki (Wiley, 2022)
Objectives
To analyze the long-term side effects of radiation therapy (RT) for head and neck cancer (HNC).
Methods
Retrospective chart analysis of all 688 HNC patients treated during 2010–2015 at Turku University Hospital, Finland. All patients who survived for more than a year after RT/chemoRT were included (n = 233). Intensity modulated RT (IMRT) with standard fractionation was applied in each case.
Results
One hundred and six patients (45%) reported persisting dysphagia, for which neck RT increased risk. Definitive neck RT to high-risk volume did not increase late toxicity risks compared to elective neck RT. Radiation-induced hypothyroidism (29%, n = 67) was more common among younger patients and females. Osteoradionecrosis (12%, n = 29) was more common in the oral cavity cancer group (20.7%, n = 92) compared to all other subsites.
Conclusions
Late toxicities of RT for HNC are common. Age, gender, tumor subsite, and neck RT affect susceptibility to long-term side effects.
Level of evidence
4.